Peran Dewan Syariah Nasional Majelis Ulama Indonesia dalam Mendorong Implementasi Standar Akuntansi Syariah pada Industri Perbankan Syariah - Muhammad Fadli Azim; Trisna Taufik Darmawansyah; Yani Aguspriyani; Surahman Surahman (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2022)
The Islamic banking industry in Indonesia has grown rapidly in recent years. This growth is supported by the increasing number of people who choose to use Islamic banking services because of their adherence to sharia principles. However, there are still a number of challenges faced by the Islamic banking industry, including in terms of Islamic accounting. Therefore, this study aims to analyze the role of DSN MUI in encouraging the implementation of sharia accounting standards in the sharia banking industry in Indonesia. This study uses a qualitative descriptive method with data collection techniques through literature studies and interviews with relevant informants. The results show that the DSN MUI plays an important role in developing sharia accounting standards in Indonesia and strengthening the oversight of compliance with sharia principles in the sharia banking industry. DSN MUI also plays a role in providing sharia advice and fatwas needed to facilitate the implementation of sharia accounting standards in the sharia banking industry. This study recommends that the DSN MUI must continue to strengthen its role and function in facilitating the application of sharia accounting standards in the sharia banking industry. In addition, there is also a need for closer coordination and cooperation between the DSN MUI, regulators, and the Islamic banking industry to ensure proper and accurate application of Islamic accounting standards in the Islamic banking industry in Indonesia.